Giant reduction of thermal conductivity and enhancement of thermoelectric performance in twinning superlattice InAsSb nanowires. (1st December 2022) - Peri, Lorenzo; Prete, Domenic; Demontis, Valeria; Zannier, Valentina; Rossi, Francesca; Sorba, Lucia; Beltram, Fabio; Rossella, Francesco
Abstract: Semiconductor nanostructures hold great promise for high-efficiency waste-heat recovery exploiting thermoelectric energy conversion. They could significantly contribute to the implementation of environmentally friendly energy sources and to the realization of self-powered biomedical wearable devices. A crucial thermoelectric material requirement is a reduced thermal conductivity together with good electrical transport properties. In this work we demonstrate a drastic reduction of the thermal conductivity in III-V semiconductor nanowires as a result of the introduction of periodic crystal-lattice twin planes during growth. The electrical and thermal transport of these nanostructures, known as twinning superlattice nanowires, are probed and compared with their twin-free counterparts, showing a one order of magnitude decrease of thermal conductivity while maintaining unaltered electrical-transport properties and Seebeck coefficients. This leads to tenfold enhancement of the thermoelectric figure of merit, ZT. Our study reports for the first time the complete experimental measurement of electrical and thermal properties in twinning superlattice nanowires, demonstrating their emergence as a novel class of nanomaterials of great potential for high-efficiency thermoelectric-energy harvesting. Graphical Abstract: ga1 Highlights: Twinning superlattice InAsSb nanowires: first electrical & thermal properties measurement. Combined ultralow thermal conductivity, excellent electrical parameters: first evidence. Tenfold enhancement of thermoelectric figure of merit: experimental demonstration. Record low thermal conductivity – record high ZT – within III-V semiconductor nanowires.